Comparison of magnetic resonance imaging findings in 880 temporomandibular disorder patients of different age groups: a retrospective study - Chuanjie Li; Qingbin Zhang (BMC, 2022)
Abstract Background Magnetic resonance imaging (MRI) findings of temporomandibular joint (TMJ) in temporomandibular disorder (TMD) patients of different ages are still unclear. The aim of this study was to analyze and compare the characteristics of MRI features of TMJs in different age groups. Methods A total of 1760 TMJs from 880 patients were included in the study and divided into three groups: ≤ 18Y (n = 195, 14.89 ± 2.35Y); 19-30Y (n = 475, 24.09 ± 3.23Y); and > 30Y (n = 210, 41.73 ± 10.45Y). T2-weighted image (T2WI) of MRI was obtained to evaluate the relationship between age and disc morphology, the degree of disc displacement, joint effusion, joint movement and changes of condylar bone morphology. Data were analyzed by Pearson Chi square test and Spearman correlation coefficient. Results There was no statistical difference between left and right sides in all age groups. Except condylar morphology (χ2 = 0.943, P = 0.624), there were significant differences in the distribution of disc morphology, disc position, joint effusion and joint motion among different age groups (χ2 = 24.450, χ2 = 24.829, χ2 = 19.855, χ2 = 39.259, respectively). There were significant differences in the distribution of the degree of anterior disc displacement, condyle morphology and joint effusion in different types of disc morphology among the different age groups (except for joint effusion in > 30Y), among which the first two were significantly correlated with the disc morphology. Conclusions The morphology and position of the articular disc changed significantly with age, but the proportion of abnormal condylar bone remained about 50%. The greater the degree of disc folding, the more prone to bone abnormalities. Trial registration This study was retrospectively registered on 28/03/2022 and endorsed by the Ethics committee (LCYJ2022014).